The characterization of a large multi-axis ionization chamber array in a 1.5 T MRI linac. (9th November 2018) - Perik, T J; Kaas, J J; Greilich, S; Wolthaus, J W H; Wittkamper, F W
Abstract: By combining magnetic resonance imaging (MRI) scanners and radiotherapy treatment units the need arises for new radiation measurement equipment that can be used in the magnetic field of the MRI. This study describes the investigation of the influence of the 1.5 T magnetic field from an MRI linac on the STARCHECK MAXI MR, a large 2D ionization chamber detector panel. Measurements were performed on an MRI linac and a conventional linac to investigate the behaviour of the detector panel with and without the 1.5 T magnetic field. We measured reproducibility, linearity, warm-up effect, saturation/recombination and chamber orientation. A comparison with gafchromic film was performed and the effect of motion of the panel during measurements inside a magnetic field was investigated. The reproducibility, linearity, warm-up effect, saturation/recombination show no significant deviations with or without magnetic field. An absolute difference in reading of 2.1% was found between off-axis chambers on different axes. The comparison with film shows good agreement. Spurious readings are induced while the panel is undergoing a motion in the magnetic field during measurements. The STARCHECK MAXI MR is suited for use in a 1.5 T MRI linac. Care must be taken when comparing un-normalized profiles from different axes of the detector panel and when the panel is undergoing motion during measurements.